Interview with the DG of AfricaRice - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
In this interview, Director General of Africa Rice and CGIAR Regional Director, West and Central Africa, Dr Baboucarr Manneh talks about how the CGIAR is transforming agriculture in Africa.